Bulk synchronous parallel ML with exceptions - Gesbert, Louis; Gava, Frédéric; Loulergue, Frédéric; Dabrowski, Frédéric (Future generation computer systems, 2010)
Bulk Synchronous Parallel ML is a high-level language for programming parallel algorithms. Built upon OCaml and using the BSP model, it provides a safe setting for their implementation, avoiding concurrency related problems (deadlocks, indeterminism). Only a limited set of the features of OCaml can be used in BSML to respect its properties of safety: this paper describes a way to add exception handling to this set by extending and adapting OCaml’s exceptions. The behaviour of these new exceptions and the syntactic constructs to handle them, together with their implementation, are described in detail, and results over an example are given.